2018
DOI: 10.3390/ijms19072025
|View full text |Cite
|
Sign up to set email alerts
|

Allyl Isothiocyanate Ameliorates Dextran Sodium Sulfate-Induced Colitis in Mouse by Enhancing Tight Junction and Mucin Expression

Abstract: Inflammatory bowel disease (IBD) is characterized by chronic or recurrent inflammation of the gastrointestinal tract. Even though the current strategies to treat IBD include anti-inflammatory drugs and immune modulators, these treatments have side-effects. New strategies are, therefore, required to overcome the limitations of the therapies. In this study, we investigated the anti-colitic effects of allyl isothiocyanate (AITC), which is an active ingredient present in Wasabia japonica. The DSS-induced colitis m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…The intestinal tight junction’s protein complexes link the atypical membranes between intestinal epithelial cells and act as a physical barrier, giving selective permeability. Deficiencies in tight junctions result in increased gut permeability, leading to an increased entrance of luminal antigens and contributing to intestinal inflammation [ 8 ]. IBD is one of the two most widespread diseases reflecting immune dysfunction, and another one is rheumatoid arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…The intestinal tight junction’s protein complexes link the atypical membranes between intestinal epithelial cells and act as a physical barrier, giving selective permeability. Deficiencies in tight junctions result in increased gut permeability, leading to an increased entrance of luminal antigens and contributing to intestinal inflammation [ 8 ]. IBD is one of the two most widespread diseases reflecting immune dysfunction, and another one is rheumatoid arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…Defects in the tight junctions result in increased gut permeability, which leads to an increased entrance of luminal antigens and contributes to intestinal inflammation. 1 Recent studies using an animal model of IBD induced by dextran sulfate sodium (DSS) administration have demonstrated not only activation of the inflammatory pathway, oxidative stress, and the alteration in serotonin (5-hydroxytryptamine )-producing enterochromaffin cells (EC), as are well known, but also anxiety-like and depressive-like behavior, cognitive impairment and decreased social interactions. [2][3][4][5][6] One of the most supported ideas linked IBD with central nervous system (CNS) neuroinflammation.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we reported the protective effect of AITC on intestinal epithelium in DSS-induced colitis model via increasing the tight junction and mucin expression [ 8 ]. In this study, we endeavored to examine another beneficial effect of AITC, by investigating the effects of AITC on liver.…”
Section: Discussionmentioning
confidence: 99%
“…Recent papers have further reported that the microbiota metabolizes glucosinolates into isothiocyanates such as AITC [ 6 , 7 ], highlighting the importance of the dietary intake of Cruciferae plants and the function of isothiocyanates in the human body. Previously, we reported the beneficial effects of AITC on intestinal epithelium in the dextran sulfate sodium (DSS)-induced colitis model [ 8 ]. In the current study, we intend to further study the function of AITC in liver, since the absorbed AITC first enters the liver via portal circulation and is mainly metabolized here [ 9 ].…”
Section: Introductionmentioning
confidence: 99%